PHYSICAL CONTENT OF THE PROBLEM OF DETERMINED CHAOS IN THE PROBLEM OF DISCRETE LOGISTIC FORECASTING - Shevchenko , V. L. (Problems of Informatization and Control, 2021)
The physical content of the conditions for the occurrence of deterministic chaos in solving discrete logistic equations used in the modeling of military-economic processes is investigated. The concept and conditions of "failure" of forecasting are introduced. The dependence of forecasting errors on the parameters of logistic equations is investigated. The obtained results allow to manage the quality of discrete forecasting of military-economic processes.